A Knowledge-Based Smart Trainer System for Transferring Knowledge From Coaches to Long Jump Students - Kamnardsiri, Teerawat; Khuwuthyakorn, Pattaraporn; Boripuntakul, Sirinun; Janchai, Worawit (Frontiers in Education, 2021)
Background: The constructive and specific feedback in guiding long jump athletes to improve their performance in each phase is part of the critical process for achieving desired long jump distance. However, to date, the potential approach for assisting a coach in capturing long jump movement and transferring their knowledge to long jump students is not well-established. Objectives: To investigate the performance of long jump students and evaluate transferring knowledge from coaches to long jump students using a Knowledge-Based Smart Trainer (KBST) System. Methods: Twenty-two participants (fifteen males, mean age = 15.33 ± 1.95 years; seven females, mean age = 14.57 ± 2.07 years) participated in the study. All participants were recruited from eleven sports schools in Thailand. Each participant was instructed to perform the long jump movement, including running, take-off, and landing, for three attempts (Test 1, Test 2, and Test 3). Test 1 was the conventional approach (coaches provided the feedback based on their experience). Test 2 and Test 3 were the KBST system approach (coaches provided the feedback based on the results from KBST system). Two cameras were used to record the participant movement from the starting position to the landing position. The capture data were analyzed by KBST system program. The outcome measures were starting position, maximum velocity, maximum velocity position, and take-off angle. Repeated-Measures ANOVA was conducted to compare the long jump performance across the three trials. The statistical significance was set at p-value < 0.05. Results: There was a statistically significant difference between Test 1 and Test 3 for long jump distance (mean difference = 0.292; Std. Error = 0.129; Sig. = 0.34). However, the mean of take-off angle was similar across the three trials (Test 1 = 12.16°, Test 2 = 12.71°, and Test 3 = 12.95°, respectively). Conclusion: The KBST system was effective in improving long jump students’ performance and also transferring knowledge from the coach to long jump students.